'Dancing the Four Directions': The spirit of intuition. Issue 2 (1st September 2017) - Jones, Rosalie M.
Among the Anishinaabe of the Great Lakes region, the Medicine Circle is a teaching tool through which to discover the gifts of our world and one's relationship with them. These teachings could fill many western books, but with Native Peoples, it is left to the individual, with guidance from Elders, to understand aspects of each direction and allow that wisdom to assist in developing Mno-Bimazdiwin – 'the good life'. In 2016, Daystar/Rosalie Jones met the challenge of creating a contemporary 'Native modern dance' inspired by the teachings of the Anishinaabe Medicine Circle. This is the story of her creative process.